Network semantic-topological model of electrogenesis - B. Lobasyuk; L. Bartsevich; A. Zamkova (Kazimierz Wielki University, 2023)
A network semantic-topological model of electrogenesis is proposed. This line of research can be considered as network neurophysiology. When building the model, using the calculation of multiple linear regression coefficients, we studied the interactions (functional relationship) between the amplitudes of EEG rhythms in the entire lead between different EEG rhythms and within the same rhythm between different EEG leads in right-handed and left-handed. Multiple regression equations were geometrically interpreted using polycyclic multigraphs. As a result of the conducted research and calculations, it turned out that left-handed people have more multiple regression coefficients, both when calculating within the limits of a complete lead between different EEG rhythms, and within the limits of one rhythm between different EEG leads. It is assumed that the central-parietal leads C3-P3 are the center of influence of generators of various EEG rhythms in the left hemisphere, both in right-handed and left-handed people. The obtained results indicate that beta-LF and beta-HF rhythms are the control integrative rhythms of electrogenesis in right-handed people in the left hemisphere and in left-handed people in both hemispheres. The controlling integrative rhythm in right-handed people in the left hemisphere is the delta rhythm.